Proteomics profiling asthma induced-lysine acetylation - Su, Xin-ming; Ren, Yuan; Li, Meng-lu; Bai, Shi-yao; Yu, Na; Kong, Ling-fei; Kang, Jian (IfADo - Leibniz Research Centre for Working Environment and Human Factors, Dortmund, 2020)
Asthma is a chronic inflammatory disease that has been extensively studied for many years. However, finding a complete cure remains a significant challenge. Protein acetylation, especially histone acetylation, plays a significant role in the anti-asthma process. Histone deacetylation inhibitors (HDACi) have been shown to have a curative effect on asthma in clinical practice. An asthmatic mouse model was created by ovalbumin induction. Proteome and acetylproteome analysis were performed on lung tissues. HDACi were tested in the asthmatic mice. A total of 5346 proteins and 581 acetylation sites were identified, among which 154 proteins and 68 acetylation peptides were significantly altered by asthma. Many activated and deactivated processes, pathways, and protein groups were identified through bioinformatics analysis. Sequence motif preference analysis gave rise to a novel Kac-related core histone region, -KAXXK-, which was postulated as a key regulatory unit of histone acetylation. Asthma involves a variety of proteome dynamics and is controlled by protein lysine acetylation through the core motif -KAXXK-. These findings provide novel avenues to target and treat asthma.
EXCLI Journal;Vol. 19 2020
Keywords: Asthma; Acetylation; Acetylproteome; HDACi; 610